A shock front at the radio relic of Abell 2744. Issue 2 (16th June 2016) - Eckert, D.; Jauzac, M.; Vazza, F.; Owers, M. S.; Kneib, J.-P.; Tchernin, C.; Intema, H.; Knowles, K.
Abstract: Radio relics are Mpc-scale diffuse radio sources at the peripheries of galaxy clusters which are thought to trace outgoing merger shocks. We present XMM–Newton and Suzaku observations of the galaxy cluster Abell 2744 ( z = 0.306), which reveal the presence of a shock front 1.5 Mpc east of the cluster core. The surface-brightness jump coincides with the position of a known radio relic. Although the surface-brightness jump indicates a weak shock with a Mach number M=1.7_-0.3^+0.5, the plasma in the post-shock region has been heated to a very high temperature (∼13 keV) by the passage of the shock wave. The low-acceleration efficiency expected from such a weak shock suggests that mildly relativistic electrons have been re-accelerated by the passage of the shock front.